Case report: Pathological complete response to perioperative treatment of radiotherapy combined with angiogenesis inhibitor in a patient with pleomorphic liposarcoma - Zhang, Chenlu; Liu, Wenshuai; Wang, Binliang; Zhu, Na; Guo, Xi; Wang, Zhiming; Zhuang, Rongyuan; You, Yang; Zhang, Yong; Tong, Hanxing; Lu, Weiqi; Zhou, Yuhong (Frontiers in Oncology, 2023)
Background Liposarcomas (LPS) are mesenchymal malignancies with four principal subtypes presenting distinct molecular and clinical features. Pleomorphic liposarcoma (PLPS) is one of the rarest and most aggressive subtypes of LPS. Surgical resection is currently a preferred curative approach for localized PLPS. However, the prognosis of unresectable PLPS is extremely poor, and there is no standard treatment. Case presentation A 59-year-old Chinese woman was diagnosed with unresectable PLPS. The case was discussed and managed by specialists from a multidisciplinary team at Fudan Zhongshan Hospital. Preoperative radiotherapy (RT) of intensity-modulated radiation therapy (IMRT) at 50 Gy/25 Fx concurrently with the angiogenesis inhibitor anlotinib (8 mg, days 1–14, every 3 weeks) was prescribed to the patient. The dosage of anlotinib was increased to 10 mg after RT. After 6 months of treatment, the tumor had significantly shrunk and was successfully resected. Examination of the surgical specimens showed a pathological complete response (pCR). Until the latest follow-up (April 2022), no recurrence was observed, and disease-free survival has exceeded 14 months. Conclusion This case sheds light on the probability that perioperative RT combined with an angiogenesis inhibitor can be effectively used in PLPS, which is resistant to chemotherapy and usually considered to have a poor prognosis. Further studies with randomized controlled clinical trials will improve our knowledge of this preoperative treatment strategy.